Pengaruh Kecerdasan Emosional dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Dinas Kesehatan Kota BanjarPengaruh Kecerdasan Emosional dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Dinas Kesehatan Kota Banjar - Tri Sulistiani; Enas Enas; Aini Kusniawati (Universitas 45 Surabaya, 2024)
Banjar City Health Service employees are currently not showing maximum performance independence and proactivity. Employee performance can be influenced by emotional intelligence and work discipline. At the Banjar City Health Service, the social skills indicator (relationship management) shows that emotional intelligence is not yet at an optimal level. Additionally, there is a lack of efficiency in maintaining punctuality and adherence to schedules. The research was conducted using an explanatory survey methodology with a quantitative approach. The data analysis technique used is the Statistical Package for the Social Sciences (SPSS) program, using descriptive and regression analysis. Research findings show that (1) Emotional Intelligence has a good and big influence on employee performance within the Banjar City Health Service. Thus, there is a positive relationship between the level of emotional intelligence and the performance of Banjar City Health Service employees. (2) The level of work discipline has a beneficial and large influence on the performance of employees at the Banjar City Health Service. In other words, the more work discipline increases, the more employee performance will increase. (3) Emotional intelligence and work discipline have a good and big influence on the performance of Banjar City Health Service employees. Therefore, there is a positive relationship between the level of emotional intelligence and work discipline and employee performance at the Banjar City Health Service.